The Effect of the Covid-19 Pandemic and Macroeconomic Variables on the Jakarta Islamic Index (JII) in Indonesia Stock Exchange - Angesti, Nidia Melania; Setyadharma, Andryan (Management Analysis Journal, 2022)
This study aims to determine the impact of the Covid-19 pandemic, macroeconomic variables (interest rate, inflation, exchange rate), and world oil prices on the Jakarta Islamic Index both in the short-term and long term. The data used in this study is secondary data. This study used Error Correction Model (ECM) analysis with weekly time series data in the period March 2020 – March 2021. The results showed that in the short-term variable interest rate and the exchange rate had a significant negative effect on the JII stock index and world oil prices had a significant positive effect on the JII stock index. The Rupiah exchange rate is negative in value, but this decrease in value means appreciation (the rupiah strengthens) meaning that when the rupiah appreciates, the JII stock index increases. Meanwhile, in the long-term, the Covid-19 pandemic variable, interest rates, and the rupiah exchange rate had a significant negative effect on the JII stock index. Inflation had a significant positive effect on the JII stock index. The increase in cases of the Covid-19 pandemic has proven to affect the Indonesian stock market, especially the Jakarta Islamic Index stock index in the long term.Therefore, the government needs to implement the most effective and efficient policies in overcoming the Covid-19 pandemic that impacts the national health and economic stability of the country.